Outcome of Conventional Method for Achieving Standard Endotracheal Cuff Pressure in Patients undergoing Endotracheal Intubation - Irfan, Shahzada (Pakistan Armed Forces Medical Journal, 2026)
Objective: To measure endotracheal cuff pressure by conventional versus instrumental method in patients undergoing endotracheal intubationStudy Design: Prospective longitudinal study.Place and Duration of Study: Department of Anesthesia, Combined Military Hospital, Kharian Pakistan, Jan to Jul 2023Methodology: Patients undergoing elective surgery under general anesthesia were included in the study. Endotracheal (ETT) cuff inflation was done using the conventional syringe method, a 10 ml syringe in Group-A and a 20 ml syringe in Group-B after intubation. Patients with difficult intubation, high risk of aspiration, facial trauma, anatomical laryngotracheal abnormality, and emergency cases were excluded. Cuff pressure was measured using an aneroid manometer, adjusted, and compared in both groups. ETT cuff pressure of 20-30cm of H2O was taken as normal.Results: Two hundred and twenty patients undergoing elective surgery under general anesthesia were included, with 122(55.4%) males and 98(44.5%) females, and a mean age of 46.22±10.38 years. There was no statistical difference in gender, BMI, and ASA class among participants of both groups in which the ETT cuff was inflated using a 10ml or 20ml syringe. The mean baseline ETT cuff pressure was 35.45±3.10 cm of H2O. 96(87.3%) participants in the 10ml syringe group and 109(99.1%) participants in the 20ml syringe group had cuff pressure >30 cm of H2O (p